2021
DOI: 10.3390/microorganisms9040702
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome of a Multiethnic Community Possessed No Predominant Microbiota

Abstract: With increasing globalisation, various diets from around the world are readily available in global cities. This study aimed to verify if multiethnic dietary habits destabilised the gut microbiome in response to frequent changes, leading to readily colonisation of exogenous microbes. This may have health implications. We profiled Singapore young adults of different ethnicities for dietary habits, faecal type, gut microbiome and cytokine levels. Subjects were challenged with Lactobacillus casei, and correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Prevotella belongs to the Bacteroides order of the phylum Bacteroidetes, there was a significant negative association with a high-calorie diet and Chinese baijiu intake and a significant positive association with rice and its products. Interestingly, this result is consistent with the most recent dietary and gut microbiota research, a low-calorie diet and a higher intake of rice and its products increase the abundance of Prevotella ( Mohammadzadeh et al., 2021 ; Thwe et al., 2021 ; Losno et al., 2021 ). Currently found in metabolic studies of Prevotella, it mainly participates in carbohydrate metabolism, promoting intestinal-nutrient absorption and resisting insulin to improve glucose metabolism ( Pedersen et al, 2016 ; Aslaner et al., 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…Prevotella belongs to the Bacteroides order of the phylum Bacteroidetes, there was a significant negative association with a high-calorie diet and Chinese baijiu intake and a significant positive association with rice and its products. Interestingly, this result is consistent with the most recent dietary and gut microbiota research, a low-calorie diet and a higher intake of rice and its products increase the abundance of Prevotella ( Mohammadzadeh et al., 2021 ; Thwe et al., 2021 ; Losno et al., 2021 ). Currently found in metabolic studies of Prevotella, it mainly participates in carbohydrate metabolism, promoting intestinal-nutrient absorption and resisting insulin to improve glucose metabolism ( Pedersen et al, 2016 ; Aslaner et al., 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…One of the most recognized drivers of the gut microbiota is food. Khine et al investigated whether foods of different origins in random rotation could destabilise gut microbiota, allowing orally introduced exogenous microbes to be colonised [ 17 ]. Their research demonstrated that random rotation in food choice balances the gut microbiota profile, leading to a non-predominant enterotype, and does not alter the capability of gut microbiota to be resistant to new possible colonizers penetrated via an oral route.…”
mentioning
confidence: 99%